Infection Prevention by Behaviour Modification - Shahani, Aruna (International Journal of Infection Control, 2007)
With limited resources available to a small infection control (IC) team at Apollo Hospital, Colombo, rising nosocomial infection rates were addressed by introducing an innovative Behaviour Modification campaign. Through education, encouragement and incentive programmes, the campaign resulted in a notable improvement in attitudes to IC throughout the entire hospital. As a result the hospital nosocomial infection rate dropped by 55% from November 2005 to November 2006. The nosocomial infection rate in the Neonatal and Cardiac Surgery ICUs dropped to 0% from 10% and the device-associated infection rate in the Medical ICU dropped from 50% to 15% during the same period. A reduction in infections caused by multi-drug resistant organisms was also observed.